The Concept of Idols in Qur’an: A Semiotic Analysis of Roland Barthes - Mahmud Fajar Harahap; Nadhira Syifa Awliya; Aep Saepurrohman; Agus Karim; Mostafa Farouk Abdelaleem Muhmood (Arabiyyatī: Journal of Arabic Language Education, 2024)
This research aims to uncover the changing meanings of the concept of idols and to symbolically approach the meanings behind verses using terms such as الأصنام, الأوثان, and لأنصاب in the Quran. The background of this writing stems from the human tendency to believe in God but falter in expressing servitude to Allah SWT. Humans constantly seek the essence of God, yet errors persist from the prophetic era to the present day. There is a tendency to adhere blindly to the teachings of ancestors who inherited these mistakes. To understand this issue further, this research will utilize Roland Barthes' semiotics. The methodology involves literature review supported by descriptive analysis.  The results of semiotic research on verses and interpretations regarding the meaning of idols in the Quran, reviewed using the concepts of Jahiliyyah and Islam, will reveal a change in meaning due to the transition of certain practices from the pre-Islamic era into Islam. The concept of idols in these three terms refers to something worshiped as a manifestation, resemblance, and offering as a method of worship.